Data quality of reported child immunization coverage in 194 countries between 2000 and 2019 - Cornelius Rau; Daniel Lüdecke; Laure B. Dumolard; Jan Grevendonk; Brenton M. Wiernik; Robin Kobbe; Marta Gacic-Dobo; M. Carolina Danovaro-Holliday (Public Library of Science (PLoS), 2022)
Analyzing immunization coverage data is crucial to guide decision-making in national immunization programs and monitor global initiatives such as the Immunization Agenda 2030. We aimed to assess the quality of reported child immunization coverage data for 194 countries over 20 years. We analyzed child immunization coverage as reported to the World Health Organization (WHO) and the United Nations Children's Fund (UNICEF) between 2000-2019 by all WHO Member States for Bacillus Calmette-Guérin (BCG) vaccine birth dose, first and third doses of diphtheria-tetanus-pertussis-containing vaccine (DTP1, DTP3), and first dose of measles-containing vaccine (MCV1). We assessed completeness, consistency, integrity, and congruence and assigned data quality flags in case anomalies were detected. Generalized linear mixed-effects models were used to estimate the probability of flags worldwide and for different country groups over time. The probability of data quality flags was 18.2% globally (95% confidence interval [CI] 14.8-22.3). The lowest probability was seen in South-East Asia (6.3%, 3.3-11.8, p = 0.002), the highest in the Americas (29.7%, 22.7-37.9, p < 0.001). The probability of data quality flags declined by 5.1% per year globally (3.2-7.0, p < 0.001). The steepest decline was seen in Africa (-9.6%, -13.0 to -5.8, p < 0.001), followed by Europe (-5.4%, -9.2 to -1.6, p = 0.0055), and the Americas (-4.9%, -9.2 to -0.6, p = 0.026). Most country groups showed a statistically significant decline, and none had a statistically significant increase. Over the past two decades, the quality of global immunization coverage data appears to have improved. However, progress has not been universal. The results highlight the need for joint efforts so that all countries collect, report, and use high-quality data for action in immunization.